2017
DOI: 10.1111/and.12908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone enanthate and resistance training on myocardium in Wistar rats; clinical and anatomical pathology

Abstract: This study was performed to determine the effects of 8 weeks testosterone enanthate (TE) injection and resistance training (RT) on cardiac muscle in male Wistar rats. A total of 28 male adult Wistar rats were randomly divided into 4 groups; control + placebo, RT + placebo, TE and TE + RT. Testosterone enanthate (20 mg/kg BW, IM) and placebo (olive oil; 0.2 ml, IM) were injected twice a week for 2 months. The RT consisted of climbing (5 reps/3 sets) a ladder carrying a load suspended from the tail. The serum ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The present study found no changes in hepatic or renal function, but a decrease was observed in urea levels in the supplemented castrated group, which was of no clinical significance when considered in isolation. This corroborates the findings of previous studies, which have shown no alteration in renal function following the use of testosterone, with only a slight increase in GOT being observed, suggesting dysfunction in the hepatic metabolism (23).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found no changes in hepatic or renal function, but a decrease was observed in urea levels in the supplemented castrated group, which was of no clinical significance when considered in isolation. This corroborates the findings of previous studies, which have shown no alteration in renal function following the use of testosterone, with only a slight increase in GOT being observed, suggesting dysfunction in the hepatic metabolism (23).…”
Section: Discussionsupporting
confidence: 92%
“…The testosterone (Durateston®) dosage was determined by the results of a pilot experiment. Doses of 15, 20, 25, and 30 mg/kg (23, 24) were tested for 4 days, once a day. On the fifth day, the potential for aggressive behavior in the animals was tested by the presentation of an intruder male for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In biochemical tests, it is known that troponin isoenzymes (cTnI) and creatine kinase MB (CK-MB) are specific indicators of cell lysis and are elevated in users of anabolic steroids. 24,25 The heart rate also decreases after exercise, according to dos Santos, 26 who also reports that this may be an effect of changes in the parasympathetic nervous system, suggesting that these effects may also occur at rest in the case of sedentary mice, due to the changes already mentioned. The decrease in heart rate is a predisposing factor to cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 86%
“…The rats were familiarized with climbing a ladder (1×0.18 m, 2-cm grid, 85° incline) with weights attached to their tails to simulate resistance exercise. The RS and RI groups performed eight weeks of resistance training consisting of three sets of five repetitions, three times a week, with 1-min rest intervals between the reps and 2-min intervals between the sets (21,22). The initial weight attached to each animal's tail was 50% of its body weight and increased gradually throughout the eight weeks (22).…”
Section: Methodsmentioning
confidence: 99%
“…The RS and RI groups performed eight weeks of resistance training consisting of three sets of five repetitions, three times a week, with 1-min rest intervals between the reps and 2-min intervals between the sets (21,22). The initial weight attached to each animal's tail was 50% of its body weight and increased gradually throughout the eight weeks (22). Subjects in the C and II groups did not perform any exercise.…”
Section: Methodsmentioning
confidence: 99%